2018
DOI: 10.1029/2018jc014161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Surface Ice Lid on the Optical Properties of Melt Ponds

Abstract: To investigate the influence of a surface ice lid on the optical properties of a melt pond, a radiative transfer model was employed that includes four plane‐parallel layers: an ice lid, a melt pond, the underlying ice, and the ocean beneath the ice. The thickness Hs and the scattering coefficient σs of the ice lid are altered. Variations in the spectral albedo αλ and transmittance Tλ due to Hs for a transparent ice lid are limited, and scattering in the ice lid has a pronounced impact on the albedo of melt pon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Solar radiation plays a key role in breaking up lake ice by melting at the surface and in the interior, warming under-ice water, and triggering convection cells under ice (Leppäranta et al 2003(Leppäranta et al , 2019Kirillin et al 2012;Salonen et al 2015;Lu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar radiation plays a key role in breaking up lake ice by melting at the surface and in the interior, warming under-ice water, and triggering convection cells under ice (Leppäranta et al 2003(Leppäranta et al , 2019Kirillin et al 2012;Salonen et al 2015;Lu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These lakes are normally ice-covered for 4-6 months with the maximum ice thickness around 50 cm with 10-20 cm of snow on top. Many studies have also been performed on Arctic sea ice (e.g., Smith and Baker 1981, Grenfell and Maykut 1997, Perovich, 1998Light et al 2008;Lu et al 2018). Although sea ice is optically different from lake ice, the results provide good reference for research on lake ice.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in ∆T i can be further analyzed based on the total daytime heat flux, from 8:00 to 16:00, because ∆T i also represents the rise of ice temperature during the daytime. The total heat flux mainly included the net surface heat flux (Q 0 ), lake ice internal heating (Q i ), and ice bottom heat flux (Q b ), calculated by Equations (1), (11) and (13), respectively. The heat required for temperature changes was calculated as follows [17,32]:…”
Section: Differences In Temperature Regime In the Winters Of 2017 Andmentioning
confidence: 99%
“…The evolution of lake ice cover is dictated by the radiation balance, turbulent heat exchange at the air-ice interface, and heat flux from the water to the ice bottom [9]. Sunlight transmittance can be higher in the ice cover than in the water because colored dissolved organic matter is mostly excluded from congelation ice [10][11][12][13]. However, the presence of an eventual snow cover always limits the penetration of solar radiation into the water due to its small optical thickness of 15-20 cm [14].…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of a single fixed melt pond spectrum could present a significant limitation to the accuracy of available algorithms, because in situ studies have shown that the optical properties of melt ponds vary considerably (Istomina et al, 2016). The broadband albedo of ponds can vary between 0.1 and 0.7 (and between 0.1 and 0.4 at red wavelengths), depending principally on the underlying ice thickness (Istomina et al, 2016; Lu, Cao, et al, 2018; Lu, Leppäranta, et al, 2018). There are, also, some MPF retrieval algorithms using Synthetic Aperture Radar (SAR) and passive microwave data, which have the advantage of all‐weather and day plus night operation.…”
Section: Introductionmentioning
confidence: 99%